Prevalence of chronic venous insufficiency and deep vein thrombosis in cirrhotic patients - da Cruz Renó, Leonardo; Tustumi, Francisco; Waisberg, Daniel Reis; Santos, Vinicious Rocha; Pinheiro, Rafael Soares; Macedo, Rubens Arantes; Nacif, Lucas Souto; Ducatti, Liliana; De Martino, Rodrigo Bronze; Trevisan, Alexandre Maximiniano; D’Albuquerque, Luiz Carneiro; Andraus, Wellington (Frontiers in Medicine, 2023)
Background & Aims: The study of chronic venous disease and its impact on patients with cirrhosis is unknown in the literature and may be an important fact since this condition also had impact on quality of life and morbidity. The aim of this study is to evaluate the prevalence of DVT (Deep Venous thrombosis) in outpatients with cirrhosis and the degree of chronic venous insufficiency, evaluating possible correlations between clinical and laboratory aspects of cirrhotic patients with these pathologies. Methods: Patients with cirrhosis were evaluated in the outpatient clinic of the Liver Transplantation and Hepatology Service of HC-FMUSP from November 2018 to November 2022, with clinical evaluation, venous disease questionnaires, data collection of imaging and laboratory tests, and venous color Doppler ultrasound. The information was analyzed by the University of São Paulo (USP) Statistics Department. Results: There was a prevalence of 7.6% of DVT in studied patients, VCSS score 6.73 and severe CEAP classification (C4-6) 32.1%. There was no association of DVT with qualitative variables by the Fisher test such as Child Turcotte Pugh Scale (CTP) (p=0.890), dichotomized INR values (p=0.804), etiology of cirrhosis (p=0.650) and chronic kidney disease (p>0.999), nor with quantitative variables by t-student such as age (p=0.974), Body Mass Index (BMI) (p=0.997), MELD score (p=0.555), Albumin (p=0.150) and Platelets (p=0.403). We found that as the severity of ascites increases, there is an increase in the proportion of patients classified in the category indicating more severe clinical manifestations of chronic venous disease (C4 to C6). The mean age (54 years) was higher in patients with DVT than in those without. Conclusions: The incidence of VTE (Venous Thromboembolic Events) and CVD (Chronic Venous Disease) within the sample surpassed that of the general population; nevertheless, more studies are required to validate these results. Concerning venous thromboembolism, no correlation was observed between the variables within the sample and the augmented risk of VTE. Regarding chronic venous disease, studies have shown that edema and orthostatism are correlated with increased severity of CVD on the VCSS scales.